HIV-1 causes an imbalance in the production of interleukin-18 and its natural antagonist in HIV-infected individuals: Implications for enhanced viral replication - Iannello, Alexandre; Boulassel, Mohamed-Rachid; Samarani, Suzanne; Tremblay, Cécile; Toma, Emil; Routy, Jean-Pierre; Ahmad, Ali (The Journal of infectious diseases, 2010)
Background. Concentrations of interleukin (IL)-18 increase in the circulation of human immunodeficiency virus (HIV)-infected persons. However, nothing is known concerning the regulation of IL-18-binding protein (IL-18BP), which neutralizes IL-18 in vivo. This issue is addressed in the present study. Methods. Serum samples obtained from healthy subjects and HIV-infected patients were analyzed by enzymelinked immunosorbent assay to determine their IL-18 and IL-18BP contents. Human monocyte-derived macrophages (MDMs) were infected in vitro with HIV type 1 (HIV-1), and the production of these 2 cytokines by these cells was measured. Finally, we determined the effect of IL-18 on HIV-1 replication in human cells. Results. In contrast to IL-18 levels, IL-18BP levels decreased in the serum of HIV-infected patients. This decrease resulted in enhanced levels of free IL-18 in the serum of such patients. The infection increased production of IL-18 but decreased that of IL-18BP in MDMs. IL-10 and transforming growth factor-β, concentrations of which are increased in HIV-infected persons, also decreased production of IL-18BP by human MDMs. Finally, recombinant human IL-18 enhanced HIV-1 replication in human CD4+ T cells. Conclusions. Production of IL-18 and its antagonist becomes imbalanced in HIV-1-infected persons. The infection and the cytokine milieu play a role in this decreased production. The increased biological activities of IL-18 may enhance viral replication in human CD4+ T cells.